Catheter ablation for non-paroxysmal atrial fibrillation. A review - Hassouna, Sabri; Osmancik, Pavel (Biomedical papers, 2024)
Atrial fibrillation (AF), the most common cardiac arrhythmia is associated with increased morbidity and mortality. The higher mortality is due to the risk of heart failure and cardioembolic events. This in-depth review focuses on the strategies and efficacy of catheter ablation for non-paroxysmal atrial fibrillation. The main medical databases were searched for contemporary studies on catheter ablation for non-paroxysmal AF. Catheter ablation is currently proven to be the most effective treatment for AF and consists of pulmonary vein isolation as the cornerstone plus additional ablations. In terms of SR maintenance, it is less effective in non-paroxysmal AF than in paroxysmal patients. but the clinical benefit in non-paroxysmal patients is substantially higher. Since pulmonary vein isolation is ineffective, a variety of techniques have been developed, e.g. linear ablations, ablation of complex atrial fractionated electrograms, etc. Another paradox consists in the technique of catheter ablation. Despite promising results in early observation studies, further randomized studies have not confirmed the initial enthusiasm. Recently, a new approach, pulsed-field ablation, appears promising. This is an in-depth summary of current technologies and techniques for the ablation of non-paroxysmal AF. We discuss the benefits, risks and implications in the treatment of patients with non-paroxysmal AF.
Keywords: atrial fibrillation; catheter ablation; radiofrequency ablation; pulmonary vein isolation